SOLUTIONS TO CHALLENGES OF ISLAMIC BANKING IN GHANA: A QUALITATIVE STUDY - IBRAHIM, ABDUL-SOMED; Yatoo, Nissar Ahmad (Universitas Airlangga, 2024)
Abstract The purpose of this study is to propose solutions to challenges affecting the take-off of Islamic banking implementation in Ghana. The research is qualitative research that uses interview to measure the opinions of a sample of 10 experts with Islamic finance background conveniently and purposively selected from higher learning/research institutions in Ghana and abroad. The data analysis is thematically done. The findings from the research propose human resource development, collaboration among stake-holders, high advocacy, comprehensive framework and top-down approach as solutions. The interviewees are dominated by Muslims and this should be considered before generalization over the entire country. Islamic banking can be implemented in Ghana if deliberate efforts are made to implement the proposed solutions. The study is the first of its kind in interviewing both local and foreign experts on solutions to the challenges of IBF in Ghana. This study will contribute to the meager literature on Islamic banking.